A Strategical Approach for Implementing Digital Games on FPGA - et. al., Sk.Irfan Ali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Field Programmable Gate Arrays (FPGAs) are providing potential solutions to the most of the technological advancements. Starting from the basic modeling of RISC and CISC processors to the complicated designs of processors for data analytics, the FPGAs are being used. Parallelism and Pipelining are the features that are enabling for its application is almost all the domains of Electronics and Communications Industry. In view of such applications, getting expertise in implementation of Digital System Designs on FPGA will become inevitable for Electronics and Communication Engineering Graduate. Learning from Gaming has proved to be successful from the very past. Inspired from the Project based learning pedagogy [15], we have come up with a novel idea of making a student learn FPGA in the process of designing and implementing a single player and two player games. The entire problem formulation of designing these games is divided into tasks and student will be learning these tasks initially. Later, integrating such tasks will evolve into games. As a part of these five games, namely Snake game, Spaceman game, Pacman game, Tic-Tac-Toe and Battle tanker games were successfully implemented on the NEXYS4 DDR FPGA Board. This implementation is done using Xilinx Vivado Software.